Electromagnetic Wave Theory and Applications - Kong, Jin Au; Ali, Sami M.; Atkins, Robert G.; Chang, Ike; Gu, Qizheng; Habashy, Tarek M.; Lee, Check-Fu; Li, Kevin; Poh, Soon Y.; Tsuk, Michael J.; Tulintseff, Ann N.; Yang, Ying-Ching Eric; et al. (Research Laboratory of Electronics (RLE) at the Massachusetts Institute of Technology (MIT), 1988)
Contains table of contents for Section 3, research summary and reports on six research projects. Joint Services Electronics Program (Contract DAAL 03-86-K-0002) Joint Services Electronics Program (Contract DAAL 03-89-C-0001) U.S. Navy - Office of Naval Research (Contract N00014-86-K-0533) National Science Foundation (Contract ECS 86-20029) U.S. Army Research Office (Contract DAAL03 88-K-0057) International Business Machine Corporation Schlumberger-Doll Research National Aeronautics and Space Administration (Contract NAG 5-270) U.S. Navy - Office of Naval Research (Contract N00014-83-K-0258) National Aeronautics and Space Administration (Contract NAG 5-769) U.S. Army Corps of Engineers - Waterways Experimental Station (Contract DACA39-87-K-0022) Simulation Technologies U.S. Air Force - Rome Air Development Center (Contract F19628-88-K-0013) U.S. Navy - Office of Naval Research (Contract N00014-89-J-1107) Digital Equipment Corporation